Coupling of the Functional Stability of Rat Myocardium and Activity of Lipid Peroxidation in Combined Development of Postinfarction Remodeling and Diabetes Mellitus - S. A. Afanasiev; D. S. Kondratieva; T. Yu. Rebrova; R. E. Batalov; S. V. Popov (Journal of Diabetes Research)
Coupling of the functional stability of rat myocardium and activity of lipid peroxidation processes in combined development of postinfarction remodeling and diabetes mellitus has been studied. The functional stability of myocardium was studied by means of the analysis of inotropic reaction on extrasystolic stimulus, the degree of left ventricular hypertrophy, and the size of scar zone. It was shown that in combined development of postinfarction cardiac remodeling of heart (PICR) with diabetes mellitus (DM) animal body weight decreased in less degree than in diabetic rats. Animals with combined pathology had no heart hypertrophy. The amplitude of extrasystolic contractions in rats with PICR combined with DM had no differences compared to the control group. In myocardium of rats with PICR combined with DM postextrasystolic potentiation was observed in contrast with the rats with PICR alone. The rats with combined pathology had the decreased value of TBA-active products. Thus, the results of study showed that induction of DM on the stage of the development of postinfarction remodeling increases adaptive ability of myocardium. It is manifested in inhibition of increase of LPO processes activity and maintaining of force-interval reactions of myocardium connected with calcium transport systems of sarcoplasmic reticulum of cardiomyocytes.